2017
DOI: 10.5194/hess-21-1039-2017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid surface-water volume estimations in beaver ponds

Abstract: Abstract. Beaver ponds are surface-water features that are transient through space and time. Such qualities complicate the inclusion of beaver ponds in local and regional water balances, and in hydrological models, as reliable estimates of surface-water storage are difficult to acquire without time-and labour-intensive topographic surveys. A simpler approach to overcome this challenge is needed, given the abundance of the beaver ponds in North America, Eurasia, and southern South America. We investigated wheth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
0
36
1
Order By: Relevance
“…In total, we estimate that wolves altered the establishment of ~88 ponds per year (95 and 99% nonparametric bootstrap CI = 36 to 162 ponds and 24 to 194 ponds, respectively) and the storage of ~194,000 m 3 of water per year [95% CI = 79,100 to 355,900 m 3 ; this assumes 2197 m 3 of water stored per pond (44)]. Notably, CIs generated via the nonparametric and parametric bootstrap approaches were nearly identical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, we estimate that wolves altered the establishment of ~88 ponds per year (95 and 99% nonparametric bootstrap CI = 36 to 162 ponds and 24 to 194 ponds, respectively) and the storage of ~194,000 m 3 of water per year [95% CI = 79,100 to 355,900 m 3 ; this assumes 2197 m 3 of water stored per pond (44)]. Notably, CIs generated via the nonparametric and parametric bootstrap approaches were nearly identical.…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the volume of surface water wolves displaced by preventing beaver pond creation and recolonization by multiplying the number of ponds wolves altered by the average volume of water stored in beaver ponds in the GVE [2197 m 3 per pond; (44)]. We used this singular estimate of surface water storage from Karran et al (44)-who only measured a small sample of ponds-to coarsely estimate the overall magnitude of the effect wolves have on water storage; a more intensive study would be needed to provide a more precise estimate of the surface water volume wolves displace each year by killing dispersing beavers.…”
Section: Impact Of Wolf Predation On Pond Creation and Water Storagementioning
confidence: 99%
“…The average values of parameter b are derived from [25] for each reservoir category. Reservoir morphometry can be assessed by computing many different variables [23]. Among them, in our study, we used the bathymetric capacity Bwc and the morphometry coefficient p.…”
Section: Volume-depth Morphometry Approximationmentioning
confidence: 99%
“…As the storage of the reservoir is often highly correlated with surface area [17][18][19] or depth [20][21][22], empirical volume-area-depth relationships can be estimated by using remotely sensed maximum water areas and reservoir characteristics. These relationships are responsible for flood routing, hydropower generation and reservoir classification [23]. The more complex the morphometry of a reservoir is, the more difficult it is to establish such a relationship [24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mineral soil environments have shown that, above the ground surface, beaver dams increase surface water area and storage (Hood & Bayley, 2008;Karran, Westbrook, Wheaton, Johnston, & Bedard-Haughn, 2017), thereby enhancing groundwater-surface water interactions (Majerova, Neilson, Schmadel, Wheaton, & Snow, 2015;Puttock, Graham, Cunliffe, Elliott, & Brazier, 2017). This can induce changes below the surface by raising water tables such that groundwater flowpaths readjust and more recharge to underlying aquifers is possible (Lowry, 1993;Westbrook, Cooper, & Baker, 2006).…”
Section: Introductionmentioning
confidence: 99%